Pengaruh Kondisi Modal Kerja Terhadap Profitabilitas (Studi Empiris : pada Perusahaan Manufaktur yang Terdaftar pada BEI Katagori Saham LQ 45 Periode 2007 sampai dengan 2011) - Hermansyah Hermansyah (Transparansi : Jurnal Ilmiah Ilmu Administrasi, 2017)
The purpose of this research is empirically to examine the effect of working capital which is based on financial ratio and will give influence partially or simultaneously to the manufacturing stocks of LQ45 at Indonesia Stock Exchange. Financial ratios which are used to determine the condition of working capital are current ratio, working capital turnover ratio, current assets to total assets ratio and current liabilities to total assets ratio which are used as dependent variable is return on investment.The data research collected from 10 manufacture’s company in LQ45 stocks category and listed in Indonesia Stock Exchange. Data collected from financial report from year ended 2007 to 2011. The final results shows that current ratio, working capital turnover ratio, current assets to total assets ratio, and current liabilities to total assets ratio are influence simultaneously to return of investment at the level of alpha (a) = 0.05 (sig 0.071)